Fatal Overdose due to Confusion of an Transdermal Fentanyl Delivery System - Ingo Voigt (Case Reports in Critical Care)
Background. The use of transdermal fentanyl systems has increased over recent years, especially in patients with chronic pain. Large misuse potential and fatal outcomes have been described. Case Presentation. A 58-year-old patient presenting with clinical signs of opioid poisoning (hypoventilation, bradycardia, hypotension, and miosis) was admitted to our ICU. The first body check revealed a 75 mcg per hour fentanyl patch at the patient's right scapula. Some months ago, patient's aunt died after suffering from an oncological disease. During breaking up of her household, the patches were saved by the patient. Not knowing the risk of this drug, he mistook it as a heat plaster. Investigations. Laboratory test showed an impaired renal function and metabolic acidosis. Urine drug test was negative at admittance and 12 h later. CCT scan presented a global hypoxic brain disease. Treatment and Outcome. The patient was discharged 30 days after admittance in a hemodynamic stable condition but a vegetative state and transferred to a rehabilitation center. Learning Points. With the ongoing increase in fentanyl patch prescriptions for therapeutic reasons, it is likely that misuse cases will become more relevant. Conventional urine drug screening tests are not able to exclude the diagnosis fentanyl intoxication. History taking should include family member's drug prescriptions.